Coaching Association of Canada
The Coaching Association of Canada (CAC) is a not-for-profit organization with the mission to establish education, training and ethical standards for coaches in Canada. Established in 1971, the Coaching Association of Canada (CAC) has the mission to "enhance the experience of all Canadian athletes through quality coaching." The HQ of the CAC ist located in Gloucester, Ontario. The homepage contains information on: - What's New - Programs - 3M National Coaching Certification Program (3M NCCP) - Canadian Professional Coaches Association (CPCA) - CAC Partners / Theory Courses - Seminars and Conferences - Product Information